Interrelations of pleasure deficiency, dopamine high secretion and overconsumption of saccharin on sprague dawley rats - Zakaria, Toumi (2020)
Emotional eating is an overeating, for compensating emotional deficiency or for relieving negative emotions that is activated by dopamine. Dopamine neurons are known for their strong responses to rewards like foods and their critical role in positive motivation. Emotional hunger elicits overeating. However, a link between emotional deficiency, dopamine activation, and overeating has not been established yet. The goal of this research is to identify the relation between the previous parameters by focusing on pleasure deficiency as a type of emotional deficiency, beta-endorphin as a pleasure neurotransmitter, and overconsumption of saccharin as an eating disorder. ELISA method was used for dopamine measurements during hunger, fullness, before tasting saccharin, and after tasting saccharin in rats’ striatum homogenate, while it was used for Beta-endorphin before and after tasting liquid saccharin in rats’ striatum homogenate, to assess their contributions in this type of emotional eating. Results showed that less dopamine is released in full rats and less beta-endorphin is released before liquid saccharin tasting and vice versa. It is proposed that dopamine is involved in the motivation of food intake, while beta-endorphin is involved in pleasure emotion of saccharin intake. Subsequently, full rats were injected subcutaneously with dopamine agonist (quinpirole) and antagonist (raclopride). Quinpirole increased liquid saccharin intake while raclopride decreased it. Food preference was observed in rats during food deprivation and satiety by using two choices of food, Mazuri high fat diet that contains fats without sweet taste represents the caloric part, and liquid saccharin as non-nutritive sweetener that contains sweet taste without any calories represents the pleasure part. Here, two different choices of food with opposite properties were used to compare between caloric and pleasure needs. All hungry rats chose Mazuri high-fat diet to compensate their caloric needs, while all full rats chose liquid saccharin to compensate their pleasure needs. These results suggest that pleasure deficiency stimulates striatum dopamine secretion, that leads to overconsumption of saccharin even though rats are full, to compensate the deficiency.